2022
DOI: 10.1136/bmjresp-2021-001194
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in recipients after lung transplant: single-centre experience and literature review

Abstract: IntroductionLung cancer is a major challenge facing modern medicine. It is the leading cause of cancer-related death in the USA. Little is known of the incidence, prevalence and disease characteristics in lung transplant recipients, a population unique in its vulnerability and exposure to carcinogenic risk factors. We aimed to elaborate these characteristics of lung cancer in our population through a retrospective cohort study.MethodsWe retrospectively reviewed our institution’s 8-year experience with lung tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Though in our case report, this lady clearly had no history of present or past smoking in any form. In a retrospective study that included posts‐lung transplant patients in Philadelphia, USA, during a period of 8 years, it was found that the mean time from lung transplant to the diagnosis of lung cancer was 24.2 months 6 . There is no reported incidence of developing lung cancer after a prolonged period of 17 years, as in our case report.…”
Section: Discussionsupporting
confidence: 53%
“…Though in our case report, this lady clearly had no history of present or past smoking in any form. In a retrospective study that included posts‐lung transplant patients in Philadelphia, USA, during a period of 8 years, it was found that the mean time from lung transplant to the diagnosis of lung cancer was 24.2 months 6 . There is no reported incidence of developing lung cancer after a prolonged period of 17 years, as in our case report.…”
Section: Discussionsupporting
confidence: 53%
“…Another patient developed ARDS after radiation pneumonitis from chemoradiotherapy. Although the number of patients is small, 2 of 12 treated patients (17%) developed posttreatment ARDS, indicating a challenging treatment course of posttransplant lung cancer, which needs increased awareness for close clinical monitoring and imaging assessment after therapy 18 …”
Section: Discussionmentioning
confidence: 99%
“…11,12 Most of the patients with posttransplant lung cancer in the present study had smoking history (85%), IPF as underlying lung disease (47%), tumors in the native lung (80%), and histology of squamous cell carcinoma followed by adenocarcinoma (40% and 33%, respectively), which were similar to the previous studies. 11,12,17,18 The high incidence of squamous cell carcinoma in the native fibrotic lung may be explained by local inflammations resulting in the increased probability of squamous metaplasia in the fibrotic area. 19,20 No clinical characteristics except for SLTx were associated with the development of posttransplant lung cancer in the present study, which may be due to the cohort size.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there may be problems with ventilating the patient at the intensive care unit, as most of the perfusion will go to the transplanted lung, in preference to the native lung, leading to ventilation/perfusion mismatch and hyperinflation of the native lung, which may prolong weaning. Infection of the native lung may be more difficult to treat and the risk of cancer in the native lung is increased to 7–10% during follow-up [ 39 , 40 ], which carries a bad prognosis [ 40 , 41 ]. In a recent study encompassing 72 single LTxs for COPD, there was no difference in 30-day survival in patients with or without early native lung complications, although the late survival was significantly worse in the patients who developed late native lung complications (5-year survival 50% versus 80%) [ 42 ].…”
Section: Choice Of Surgical Proceduresmentioning
confidence: 99%
“…Infection of the native lung may be more difficult to treat and the risk of cancer in the native lung is increased to 7-10% during follow-up [39,40], which carries a bad prognosis [40,41]. In a recent study encompassing 72 single LTxs for COPD, there was no difference in 30-day survival in patients with or without early native lung complications, although the late survival was significantly worse in the patients who developed late native lung complications (5-year survival 50% versus 80%) [42].…”
Section: Evaluation and Preparationmentioning
confidence: 99%